Peran Komunikasi Pembangunan Agama Dalam Pembentukan Taman Pendidikan Al-Qur’an (TPA) Keliling (Study Kasus Desa Adiluwih Kabupaten Pringsewu Provinsi Lampung) - tofa pamuka aji, Mike Meiranti (Universitas Muhammadiyah Kotabumi, 2024)
Indonesia is a country that has a large religious foundation, therefore every aspect of Indonesian society's life must be based on religious foundations, especially in the field of communication. Communication is a primary activity in every human life, in communication there is an applied concept that is very important for human progress, namely the concept of development. In the practice of communication, it must have a development concept in it, so that the discipline of development communication emerges. Development communication is a communication science discipline that forms development concepts aimed at improving the quality of life of society, namely by increasing human resources using basic development concepts. Religious development communication offers an important role in instilling religious values, especially in childhood, the role of religious development communication is the beginning of forming good patterns of religious application for children. TPA is a forum that must maximize its role in instilling religious understanding in children. TPA not only teaches religious spiritual practices, but aspects of religious life must begin to be taught at TPA, therefore the communication process for religious development can be maximized in the management of TPA as a means for children to develop religious values. Mobile TPA is the latest innovation as a learning tool. Mobile TPA prioritizes the principle of friendship because in the process, TPA activities are carried out in students' homes alternately, so that it can create familiarity and feelings of sympathy and empathy in students, so that Islamic values in terms of muamalah little by little begin to be familiarized from childhood, namely the concept of friendship.